Contrasting genetic effects of red mangrove (Rhizophora mangle L.) range expansion along West and East Florida. (22nd June 2016) - Kennedy, John Paul; Garavelli, Lysel; Truelove, Nathan K.; Devlin, Donna J.; Box, Stephen J.; Chérubin, Laurent M.; Feller, Ilka C.
Abstract: Aim: We evaluated underlying mechanisms and genetic effects of climate‐driven range expansion of Rhizophora mangle L., a coastal foundation species, along both West (WFL) and East (EFL) Florida, USA. Location: Eight sites encompassing the entire Florida R. mangle range at a regional scale. Methods: We characterized R. mangle population genetic structure with a combination of genetic analyses using seven microsatellite loci and model‐based propagule transport. We tested hypotheses on the genetic effects of range expansion along both WFL and EFL. Finally, we compared WFL and EFL range edges and assessed potential factors shaping observed differences. Results: Regional‐scale Florida R. mangle genetic structure is shaped in part by the non‐independent effects of geographical distance and ocean currents that drive asymmetric propagule transport from WFL to EFL. WFL conformed to theoretical expectations of range expansion, with pronounced divergence at the range edge, whereas EFL deviated from expectations. Significant differences in diversity and differentiation at the WFL and EFL range edges were attributed to differences in migration rates, population size and founder effects. Main conclusions: Contrasting genetic landscapes at the WFL and EFL range edges are in part the product of variation in ocean circulation and demographic history. These underlying mechanisms may have potential ecological and evolutionary consequences that need to be addressed with further empirical research.